Astragalus Polysaccharide Mitigates Rhabdomyolysis-Induced Acute Kidney Injury via Inhibition of M1 Macrophage Polarization and the cGAS-STING Pathway - Sun C; Zhao X; Wang X; Yu Y; Shi H; Tang J; Sun S; Zhu S (Journal of Inflammation Research)
Chuanchuan Sun,1,2 Xinhai Zhao,1 Xianghong Wang,3 Yeye Yu,1 Heng Shi,4 Jun Tang,5 Shengyun Sun,1 Shiping Zhu1 1Department of Traditional Chinese Medicine, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 2Department of Nephrology, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 3Department of Endocrinology and Metabolism, Zhuhai People’s Hospital (Zhuhai Clinical Medical College of Jinan University), Zhuhai, People’s Republic of China; 4Department of Gastroenterology, The Central Hospital of Shaoyang, Shaoyang, People’s Republic of China; 5The Fifth Affiliated Hospital of Zunyi Medical University, Zhuhai(Zhuhai Sixth People’s Hospital), Zhuhai, People’s Republic of ChinaCorrespondence: Shengyun Sun; Shiping Zhu, Department of Traditional Chinese Medicine, The First Affiliated Hospital of Jinan University, No. 613 Huangpu Avenue West, Tianhe District, Guangzhou, Guangdong Province, 510630, People’s Republic of China, Email shengyunsun2020@163.com; zhushiping@jnu.edu.cnPurpose: This study aimed to examine the impact of APS on acute kidney injury induced by rhabdomyolysis (RIAKI), exploring its association with macrophage M1 polarization and elucidating the underlying mechanisms.Methods: C57BL/6J mice were randomly assigned to one of three groups: a normal control group, a RIAKI model group, and an APS treatment group. Techniques such as flow cytometry and immunofluorescence were employed to demonstrate that APS can inhibit the transition of renal macrophages to the M1 phenotype in RIAKI. Furthermore, the raw264.7 macrophage cell line was chosen and induced into the M1 phenotype to further examine the impact of APS on this model and elucidate the underlying mechanism.Results: Administration of APS led to a significant decrease in UREA levels by 25.2% and CREA levels by 60.9% within the model group. Also, APS exhibited an inhibitory effect on the infiltration of M1 macrophages and the cGAS-STING pathway in kidneys within the RIAKI, subsequently leading to decreased serum concentrations of IL-1β, IL-6 and TNF-α by 44.5%, 12.9%, and 10.3%, respectively, consistent with the results of in vitro experiments. Furthermore, APS exhibited an anti-apoptotic effect on MPC5 cells when co-cultured with M1 macrophages.Conclusion: Astragalus polysaccharide (APS) potentially mitigated rhabdomyolysis-induced renal damage by impeding the M1 polarization of macrophages. This inherent mechanism might involve the suppression of the cGAS-STING pathway activation within macrophages. Furthermore, APS could endow protective effects on podocytes through the inhibition of apoptosis.Keywords: astragalus polysaccharide, macrophages, rhabdomyolysis-induced acute kidney injury, cGAS-STING pathway